To the question of the e-government performance assessment - Marushka, Dzmitry A.; Ablameyko, Maria S.; Son, Nguyen Nhu (Journal of the Belarusian State University. Economics, 2018)
Methodical approaches to assess the e-government performance using integral and private indicators have been developed. Proposed recommendations describe the stages of conducting a comprehensive analysis and assessment of the e-government performance; include system of integrated indicators defining e-government development results and model system of key indicators for e-government performance assessment.
Keywords: e-government; system of indicators; efficiency; performance; information technologies; information society